The challenges of implementation of ERP in accounting - Knežević Goranka; Pavlović Vladan; Milačić Ljubiša (Ekonomski Pogledi, 2015)
Accounting information system can be divided into traditional system based on computers with the database allocated among divisions and integrated business application (ERP- Enterprise Resource Planning) where all divisions have access to the data needed to successfully complete their basic functions. Integrated business solutions increase business efficiency, encourage preparation of reports of a high quality and increase efficiency of decision making processes. However, not only that these ERP models and their implementation is not cost effective they also decrease employee moral because ERP solutions are seen as a method of downsizing. Only 9,9% of Serbian enterprises use ERP solutions. The goal of this paper is to point out problems and challenges of ERP implementation, but also to focus on its advantages in terms of increased efficiency of the business.